2020
DOI: 10.2147/jep.s265727
|View full text |Cite
|
Sign up to set email alerts
|

<p>Activity and Effectiveness of Recombinant hEGF Excreted by <em>Escherichia coli</em> BL21 on Wound Healing in Induced Diabetic Mice</p>

Abstract: Context: Human epidermal growth factor (hEGF) has biological activities and can be used in medicines and cosmetics. A high level of effectiveness of hEGF can be obtained when three disulfide bonds fold perfectly. Extracellular secretion from E. coli BL21 using the PelB signal peptide is a new way to obtain hEGF with a structure that folds appropriately. Object: This study aimed to determine the activity and effectiveness of recombinant hEGF excreted by E. coli BL21 on wound healing in induced diabetic mice. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…On the 8 th day, all treatments provided a higher wound closure percentage than the control group while in 10 th day all treatment have complete wound closure and significantly different from the control group. Mallory-azan staining to distinguish extracellular tissue components ( Sriwidodo et al., 2020 ) revealed that the mice treated with the hEGF-liposome-chitosan patch had thick epithelial formation, equally fibroblasts, and better collagenisation ( Figure 8 ), indicating that the refolded EGF induced wound closure.
Figure 7 Refolded EGF activity in inducing wound closure.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the 8 th day, all treatments provided a higher wound closure percentage than the control group while in 10 th day all treatment have complete wound closure and significantly different from the control group. Mallory-azan staining to distinguish extracellular tissue components ( Sriwidodo et al., 2020 ) revealed that the mice treated with the hEGF-liposome-chitosan patch had thick epithelial formation, equally fibroblasts, and better collagenisation ( Figure 8 ), indicating that the refolded EGF induced wound closure.
Figure 7 Refolded EGF activity in inducing wound closure.
…”
Section: Resultsmentioning
confidence: 99%
“…The wound was visualised using a “USB microscope” and the wound area was measured by ImageJ software on days 0, 4, 8, 10, and 12 after treatment. The percentage of wound closure was calculated using the following equation ( Sriwidodo et al., 2020 ): …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suspended cells were mixed with PCM and centrifuged, and the pellet was dissolved in fresh PCM and seeded into fresh flasks. When the adhesive surface of the culture vessel is completely covered with cultured cells and there is no room for cells to grow as a monolayer, it is considered to be confluent [29] . At 80 % confluence, the cells were harvested in a centrifuge tube with trypsin/EGTA (0.25/0.2 %, 3 min, 37 °C) and centrifuged at 1200 r/min, 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…When the adhesive surface of the culture vessel is completely covered with cultured cells and there is no room for cells to grow as a monolayer, it is considered to be confluent. [29] At 80 % confluence, the cells were harvested in a centrifuge tube with trypsin/EGTA (0.25/0.2 %, 3 min, 37 °C) and centrifuged at 1200 r/min, 5 min. Cell suspensions were prepared using low-FBS/PCM (containing 0.2 % FBS and the same remaining components as PCM) instead of PCM in 6-well plates at 4 × 10 4 cells/mL suspension.…”
Section: Cell Culture and Numbermentioning
confidence: 99%